2021
DOI: 10.3389/frobt.2021.644529
|View full text |Cite
|
Sign up to set email alerts
|

An Immersive Investment Game to Study Human-Robot Trust

Abstract: As robots become more advanced and capable, developing trust is an important factor of human-robot interaction and cooperation. However, as multiple environmental and social factors can influence trust, it is important to develop more elaborate scenarios and methods to measure human-robot trust. A widely used measurement of trust in social science is the investment game. In this study, we propose a scaled-up, immersive, science fiction Human-Robot Interaction (HRI) scenario for intrinsic motivation on human-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The studies reported below by Kerzel et al [28] and Churamani et al [9] are concerned with displaying and learning emotions, an important prerequisite for communicating non-verbal explanations when viewed through the lens of the XHRI framework. In [71], the effects of nonverbal communication on trust, a main driver for explainable AI research in HRI, are examined. The work summarized in [6] combine verbal utterances and non-verbal cues to Fig.…”
Section: Re-analysis Of Hri Experiments With Nico From An Xai Perspec...mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported below by Kerzel et al [28] and Churamani et al [9] are concerned with displaying and learning emotions, an important prerequisite for communicating non-verbal explanations when viewed through the lens of the XHRI framework. In [71], the effects of nonverbal communication on trust, a main driver for explainable AI research in HRI, are examined. The work summarized in [6] combine verbal utterances and non-verbal cues to Fig.…”
Section: Re-analysis Of Hri Experiments With Nico From An Xai Perspec...mentioning
confidence: 99%
“…Non-verbal Communication in a Cooperative Scenario: Zörner et al [71] analyzed the influence of non-verbal communication in developing trust with a robot in a cooperative scenario. In the fictional experimental scenario, two NICO robots offer information and advice to the user who has to assign (fictional) limited resources to the different actions suggested by the two robots as a measurement of trust.…”
Section: Non-verbal Communication: the Role Of Displaying And Recogni...mentioning
confidence: 99%
“…YOLOv5 is the latest and the most lightweight version of the previous YOLO algorithms and uses the PyTorch framework instead of the Darknet framework. An overview of YOLOv5 is shown in Figure 1 [ 24 ], and Table 1 summarizes the comparison between the architectures of the YOLOv3, YOLOv4, and YOLOv5 algorithms [ 29 ]. The head and neural network type are the same for all of the algorithms, whereas the backbone, neck, and loss function are different.…”
Section: Related Workmentioning
confidence: 99%
“…The technology of human–robot interaction has gradually been applied to the field of education [ 23 , 24 , 25 , 30 , 31 ]. Logan found that children were more attracted to electronic products and could concentrate and maintain their attention for longer [ 25 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation